STATUS AND PROBLEMS OF COOPERATION WITH HIGHER EDUCATIONAL ENTERPRISE ENTERPRISES. - Urinov, U. (International Journal of Psychosocial Rehabilitation, 2020)
This article presents government decisions regarding the training of students through the interaction between the higher education system and the manufacturing industry in terms of labor market requirements, and suggestions for its implementation. The importance of establishing mutually beneficial cooperation with educational institutions, employers, labor market entities and institutions, state and local authorities and public organizations in the training of competitive personnel in higher education. The need for improving the process of higher education provided by highly qualified professionals and the factors related to this need are summarized. Observations and analysis revealed problems in cooperation. The tasks that must be done to address these issues are outlined. It is stated that the profound knowledge of the scientific and pedagogical basis of the training of competitive personnel is a requirement of the time.